Changing gear: Experiences of how existing qualitative research can adapt to an unfolding health emergency - Jones, Theresa; Enria, Luisa; Lees, Shelley; Marchant, Mark; Tulloch, Olivia (Frontiers in Sociology, 2022)
Long-term research projects are not always able to adapt to a new crisis and incorporate characteristics and approaches of rapid research to produce useful data quickly. Project AViD was a programme of research that ran between 2018 and 2022 to examine factors that shape vaccine confidence. The project initially focused on five country case studies looking at vaccines for Ebola, Measles, Rift Valley Fever and Zika. The COVID-19 pandemic emerged during this time and provided an opportunity to contribute to the pandemic's ‘million-dollar question'–how to deploy COVID-19 vaccines. Drawing on our experience as researchers, and specifically from AViD, we propose seven factors that can influence when and how longer-term qualitative research projects can adapt and contribute to the response to an unfolding health emergency. These include: (1) the phase of research in which the emergency hits; (2) the relative significance of the emergency in the research setting; (3) the specific methods and research team capacities; (4) existing operational links; (5) supportive ecosystems; (6) flexibility in research contracting and funding; and (7) the research team attitude and approach. We close with two considerations for longer-term research projects that find themselves having to “change gear” amid a public health emergency–the need to re-assess risks and benefits and the need to protect equitable partnerships.